Synchronous and Asynchronous: Teaching and Learning Arabic in Building Student Well-being during Covid-19 Pandemic - Sanusi, Anwar; Maulana, Deni; Sabarno, Ripaldi (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2022)
Providing student well-being in the midst of the covid-19 pandemic is very important to achieve the objectives of teaching and learning Arabic. Lecturers as one component of education are required to have competence in managing teaching and learning processes and pleasant teaching and learning interactions with the students. Therefore, this study aimed to explore the processes of teaching and learning Arabic in private Islamic universities based on the synchronous and asynchronous basis in building student well-being. This study used a descriptive qualitative approach with three data collection techniques, namely observation, interviews, and documentation. The results of the study showed that synchronous and asynchronous-based teaching and learning in the midst of the covid-19 pandemic was able to build student well-being. It was confirmed by the number of 25 students who took part in the Arabic teaching and learning processes, 80% of students were very happy and excited about the approach and method used by the lecturer in teaching and learning Arabic. In addition, students and lecturers produce learning products, namely the Indonesian-Arabic Economics dictionary book. The results of the study are expected to be an alternative consideration for Arabic language lecturers at the university level in dealing with online lectures in the midst of the covid19 pandemic.